An Analysis Students Habit of using Body Language (Gesture) to Replace Unmastered English Vocabulary in Class Eleventh Six at SMA Negeri 1 Pematangsiantar - Raysha Zahra Harahap; Trivena Gracia Sirait; Trinita Ivana Rumapea; Dumaris E Silalahi (Jurnal Multidisiplin Sahombu, 2026)
This study investigates the habit of students using body language (gestures) to replace unmastered English vocabulary during classroom communication. Vocabulary mastery is a key component in English learning, yet many students struggle to express themselves verbally, resulting in a reliance on gestures as compensatory tools. Although previous research has shown the effectiveness of gestures in enhancing comprehension and engagement, limited studies focus on students’ natural gesture use in Indonesian EFL classroom contexts. Therefore, this study aims to analyze how eleventh-grade students at SMA Negeri 1 Pematangsiantar utilize gestures to substitute for English vocabulary they have not yet mastered. Employing a descriptive qualitative method, data were collected through classroom observations and semi-structured interviews with ten purposively selected students. The findings revealed that students frequently employed iconic, deictic, and emblematic gestures, primarily to clarify meaning and maintain communication flow when vocabulary gaps occurred. These gestures were found to facilitate comprehension, support memory retention, and sustain classroom interaction, aligning with the embodied cognition theory that emphasizes the integration of body movement in language processing. However, overdependence on gestures may hinder verbal vocabulary growth. The study concludes that gestures serve as effective nonverbal strategies in English learning, yet should be integrated with explicit vocabulary instruction to promote balanced communicative competence.